2021
DOI: 10.1021/acsinfecdis.1c00463
|View full text |Cite
|
Sign up to set email alerts
|

Benzimidazole Isosteres of Salicylanilides Are Highly Active Colistin Adjuvants

Abstract: Multidrug-resistant bacterial infections have become a global threat. We recently disclosed that the known IKK-β inhibitor IMD-0354 and subsequent analogues abrogate colistin resistance in several Gram-negative strains. Herein, we report the activity of a second-generation library of IMD-0354 analogues incorporating a benzimidazole moiety as an amide isostere. We identified several analogues that show increased colistin potentiation activity against Gram-negative bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Further modifying the amine with acylation (2) or alkylation to a complete loss of colistin-potentiating activity against both bacteria (Table 1). We next replaced the nitro group on niclosamide with an azide (4), a methy (5a), a carboxylic acid (6), various amide moieties (7)(8)(9)(10)(11)(12), and triazole fragments ( (Table 2). We observed that the azide and methyl ester derivatives retained synerg colistin against all strains tested, indicating that these modifications are compatibl the colistin potentiation of niclosamide.…”
Section: Biological Evaluations 221 Initial Screen For Synergy With C...mentioning
confidence: 99%
See 2 more Smart Citations
“…Further modifying the amine with acylation (2) or alkylation to a complete loss of colistin-potentiating activity against both bacteria (Table 1). We next replaced the nitro group on niclosamide with an azide (4), a methy (5a), a carboxylic acid (6), various amide moieties (7)(8)(9)(10)(11)(12), and triazole fragments ( (Table 2). We observed that the azide and methyl ester derivatives retained synerg colistin against all strains tested, indicating that these modifications are compatibl the colistin potentiation of niclosamide.…”
Section: Biological Evaluations 221 Initial Screen For Synergy With C...mentioning
confidence: 99%
“…Nonetheless, these findings demonstrated that the nitro gr mide can be replaced with a variety of substituents while still retaining sy istin. We next replaced the nitro group on niclosamide with an azide (4), a methyl ester (5a), a carboxylic acid (6), various amide moieties (7)(8)(9)(10)(11)(12), and triazole fragments (14-17) (Table 2). We observed that the azide and methyl ester derivatives retained synergy with colistin against all strains tested, indicating that these modifications are compatible with the colistin potentiation of niclosamide.…”
Section: Biological Evaluations 221 Initial Screen For Synergy With C...mentioning
confidence: 99%
See 1 more Smart Citation
“…This set of analogues was synthesized following the route shown in Scheme 1, utilizing appropriately substituted indoles. Incorporation of a bromo substituent at the 5′- (22) or 6′- (23) position resulted in a moderate reduction in colistin potentiation (MICs of 4 and 8 μg mL −1 , respectively) in comparison to 5, while a bromo substituent at the 7′-position (24) resulted in comparable activity (1 μg mL −1 ). Incorporation of a chloro substituent at either 5′ (25), 6′ (26), or 7′ (27) also delivered…”
Section: Synthesis and Evaluation Of Indirubin Librarymentioning
confidence: 99%
“…1). 22 Subsequent analog synthesis identified additional salicylanilide derivatives 23 as well as benzimidazole derivatives 24 (representative structures 6 and 7 ) that are more active than IMD-0354.…”
Section: Introductionmentioning
confidence: 99%